The Episciences journals: an overview - Magron, Agnès; Dandieu, Claire (Septentrio Conference Series, 2018)
Episciences (https://www.episciences.org/) is a hosting platform of open access journals created in 2013 and developed by the Center for Direct Scientific Communication (CCSD), a joint unit of French public research organisms (CNRS, INRIA, INRA and Lyon University). The Episciences project is organized with a steering committee and epi-committees, whose role is to promote the creation of editorial committees. It is built as an overlay (epi-) publishing service upon an open repository, currently arXiv and HAL. The platform is free of charge and offers a comprehensive set of tools for managing the journal, from organizing peer reviewing to disseminating its contents. Episciences allows research communities to experiment with innovative ways to publish and disseminate contents: authors first submit their preprints in an open archive and then submit them to the overlay journal of their choice. Episciences now hosts 11 journals in Mathematics, Informatics, Social and Human sciences. There are new journals originally created in Episciences and existing journals that have migrated on it. In April 2018 – five years after the launch of Episciences – the CCSD conducted a survey of the editorial teams regarding their uses of Episciences and their expectations. The survey was a Google Form sent to the chief editors of the 11 active journals. The objective was to collect at least one answer for each journal, representative of the positions of the editorial team. All the 11 teams have answered. The survey was intended to test their satisfaction, to better know how they use the main software features, and to test their opinion about emerging practices such as open peer review. The poster will present the main results of this survey. The main weakness of Episciences is the workflow imposing a two-stage submission process (in the repository and after in the journal). The strengths are the great assets of the economic model and the editorial support teams.